Nanocompósitos magnéticos para aplicações em agentes de contrastes imagiológicos bimodais e adsorção de corantes catiônicos - Rocha, Janaína Sobreira (2019)
In this work, different methodologies for the preparation of iron oxide (Fe3O4) magnetic nanoparticles (NPMs) will be presented, with subsequent association to manganese oxide sheets (MnO2) and titanate nanotubes (NTTi ), forming hierarchical structures to obtain two magnetic nanocomposites. MnO2/Fe3O4 nanosystem has been studied for applications as contrast imaging agents (ACI) in magnetic resonance imaging (MRI). On the other hand, NTTi/Fe3O4 system was applied for the adsorption of cationic dyes. All samples were characterized for particle size distribution and morphology. Additionally, for the MnO2/Fe3O4 nanosystems, relaxativit measurements and RMI were performed. The sample with the highest NPM concentration showed the highest values of relaxivities (r1Mn,GSH = 3,45 mM−1s−1 and r2Fe,H2O = 133.53 mM−1s−1), with promising use in bimodal ACI. For NTTi/Fe3O4 nanosystems, a decay on the specific surface area was observed as a function of the increase in the concentration of NPMs (from 198 to 152 m2g−1). The cationic dye adsorption isotherms on the NTTi / Fe3O4 system follow the Langmuir model for the adsorbent-adsorbate interaction. The maximum adsorption capacity (qmax) for methylene blue dye (AM) 169 mg.g−1 for NTTi as prepared, with a tendency to decrease as a function of the inversely proportional. the amount of Fe3O4 in composites. Cytotoxicity tests were performed for MnO2 / Fe3O4 samples via metabolic activity to evaluate the biocompatibility of the nanocomposites. The results obtained in this Thesis indicated that the two studied nanosystems can be applied in different areas: biomedicine and textile effluent treatment.